Thermodynamic study and transition metal (nickel) doping on Li1.2Mn0.8O2 as a cathode material - Mikosi Vusani; Malatji Kemeridge; Ngoepe Noko; Ngoepe Phuti (MATEC Web of Conferences, 2023)
Several studies have been conducted to overcome the poor cycling stability, voltage fade, and low coulombic efficiency barriers in practical applications of Lithium manganese oxides. Transition metal doping is considered as one of the effective techniques to enhance the stability of these materials. In this study we use the genetic algorithm within cluster expansion to generate new phases of Ni-doped Li1.2Mn0.8O2 which was constructed from Li2MnO3. Li2MnO3’s high energy density and high specific capacity have drawn attention to the material as a promising cathode for lithium-ion batteries. The generated phases are thermodynamically stable with negative heats of formation. Furthermore, first principles calculations were performed to study the thermodynamic, mechanical, and electronic properties of these materials. The materials were found to be thermodynamically stable with negative heats of formation and mechanically stable under the strain 0.001. Furthermore, the generated phases show an improvement on the conductivity of the Li1.2Mn0.8O2 since they do not have band gaps suggesting that they are conductors.